Recombinant human interferon gamma in the treatment of rheumatoid arthritis: double blind placebo controlled study. Issue 9 (September 1992) - Machold, K P; Neumann, K; Smolen, J S
Abstract : Interferon gamma (IFN gamma) has been advocated in open studies as a beneficial remission inducing drug for the treatment of rheumatoid arthritis (RA). The work reported here was designed to assess the therapeutic potential of IFN gamma in the treatment of RA in a double blind placebo controlled study. It was found that patients treated with IFN gamma improved significantly with respect to morning stiffness, grip strength, swelling of an index joint, and erythrocyte sedimentation rate. Furthermore significantly more responders (according to predetermined response criteria) were found in the group treated with IFN gamma. Only minor adverse effects and no significant toxicity with respect to clinical or laboratory parameters were observed.